2018
DOI: 10.1007/s10120-018-0881-3
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of thymidine phosphorylase can reverse acquired 5FU-resistance in gastric cancer cells

Abstract: Background 5FU can be converted to its active metabolite fluoro-deoxyuridine monophosphate (FdUMP) through two pathways: the orotate phosphoribosyl transferase–ribonucleotide reductase (OPRT–RR) pathway and the thymidine phosphorylase–thymidine kinase (TP–TK) pathway. We investigated the mechanism underlying 5FU-resistance, focusing on the changes in the 5FU metabolisms. Methods MKN45 and 5FU-resistant MKN45/F2R cells were treated with 5FU or fluoro-deoxyuridine (FdU) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Indeed, 5FU is actively absorbed by highly proliferating tissues, especially tumor ones, that need uracil for nucleic acid biosynthesis, and thus acts by inhibiting tumor cell division exploiting two different ways: it may inhibit the thymidylate synthase (TYMS), forming a covalent ternary complex with 5,10-methylenetetrahydrofolate, suppressing in that way the DNA synthesis, or it might be incorporated into RNA molecules blocking gene expression [ 3 ]. Once internalized into tumor cells, 5FU is converted to fluorouridine monophosphate (FUMP) by the orotate phosphoribosyltransferase (OPRT) and then converted to fluorodeoxyuridine monophosphate (FdUMP) by the ribosyl reductase complexes (RRM1/2), a biochemical process better known as the “OPRT–RR pathway” [ 4 ]. While FdUMP inhibits DNA synthesis through its inhibitory action on TYMS, FUMP is largely responsible for the inhibition of gene expression through its incorporation into mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 5FU is actively absorbed by highly proliferating tissues, especially tumor ones, that need uracil for nucleic acid biosynthesis, and thus acts by inhibiting tumor cell division exploiting two different ways: it may inhibit the thymidylate synthase (TYMS), forming a covalent ternary complex with 5,10-methylenetetrahydrofolate, suppressing in that way the DNA synthesis, or it might be incorporated into RNA molecules blocking gene expression [ 3 ]. Once internalized into tumor cells, 5FU is converted to fluorouridine monophosphate (FUMP) by the orotate phosphoribosyltransferase (OPRT) and then converted to fluorodeoxyuridine monophosphate (FdUMP) by the ribosyl reductase complexes (RRM1/2), a biochemical process better known as the “OPRT–RR pathway” [ 4 ]. While FdUMP inhibits DNA synthesis through its inhibitory action on TYMS, FUMP is largely responsible for the inhibition of gene expression through its incorporation into mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…5-FU functions by inhibiting thymidylate synthase through replacement of thymidine in DNA with fluorinated nucleotides, which in turn inhibits DNA replication causing cell death [ 165 ]. The success of 5-FU in triggering cell death is highly dependent on expression of a number of enzymes including thymidine phosphorylase and dihydro-pyrimidine dehydrogenase, which contribute to the degradation and metabolism of 5-FU, leading to drug resistance [ 166 , 167 ]. Other mechanisms contributing to resistance to 5-FU include an increased level of DNA repair [ 165 ].…”
Section: 3d Models For Determining Resistance To Therapeuticsmentioning
confidence: 99%
“…It was reported that PRPS1 was highly and specifically expressed in cisplatin-resistant human breast cancer cell lines, which could be a therapeutic approach to enhance drug responsiveness [92]. Mori et al suggested that the suppression of thymidine phosphorylase could enhance the drug responsiveness of gastric cancer cells to 5-fluorouracil [93]. Mitochondrial methylenetetrahydrofolate dehydrogenase 2 and its downstream purine synthesis pathway played an important role in the chemoresistance of lung cancer cells to gefitinib [94].…”
Section: Nucleotide Metabolismmentioning
confidence: 99%